2020
DOI: 10.1016/j.athoracsur.2020.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Dextran- Versus Crystalloid-Based Prime in Cardiac Surgery: A Prospective Randomized Pilot Study

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…The study's main results have been published elsewhere. 14 For the present secondary analysis, blood samples for analysis of five brain injury markers (GFAP, S100B, NSE, tau, and NfL) and the blood-brain barrier injury marker β-trace protein were collected from the arterial line at three time points: before surgery (after induction of anesthesia); 2 h after CPB, and 24 h after CPB. At the same time points, the degree of hemolysis was measured as it is known that hemolysis interacts with the analysis of NSE.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study's main results have been published elsewhere. 14 For the present secondary analysis, blood samples for analysis of five brain injury markers (GFAP, S100B, NSE, tau, and NfL) and the blood-brain barrier injury marker β-trace protein were collected from the arterial line at three time points: before surgery (after induction of anesthesia); 2 h after CPB, and 24 h after CPB. At the same time points, the degree of hemolysis was measured as it is known that hemolysis interacts with the analysis of NSE.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the clinical management have been published before. 14 In short, anesthesia was induced with fentanyl and propofol followed by rocuronium, and maintained with sevoflurane. The CPB circuit was primed with 1,300 mL solution according to the blood-brain barrier injury.…”
Section: Clinical Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…The promising properties of the isolated protein cocktail in hemolysis treatment were tested in vivo by administering mechanically hemolyzed blood plasma mixed with either the protein cocktail or dextran 70 kDa (Dex70) via exchange transfusion at 5% of the animal's total Hb mass. Dex70 was chosen for comparison given its improved plasma expansion properties compared to HSA, potential anti‐inflammatory effects, and interest as a pump‐priming fluid 30,31 . Ferritin levels in the heart, kidney, liver, and blood were measured, and markers of tissue inflammation or injury were also assessed.…”
Section: Resultsmentioning
confidence: 99%
“…According to the original study, the primary end‐point was the plasma oncotic pressure during CPB. A power calculation estimated that it would take 40 patients in each group to detect a 30% difference in oncotic pressure between the groups with 90% power and a significance level of 0.05 24 . A post hoc analysis revealed that the power to detect a 50% difference in peak urinary NAG/creatinine ratio was 0.65 at an SD of 4.5.…”
Section: Methodsmentioning
confidence: 99%